Gas permeability calculation of tight rocks based on laboratory measurements with non-ideal gas slippage and poroelastic effects considered. (December 2018) - Wang, Ziyan; Fink, Reinhard; Wang, Yue; Amann-Hildenbrand, Alexandra; Krooss, Bernhard M.; Wang, Moran
Abstract: Permeability measurements on low-permeable rocks in the laboratory require much higher pressure gradients than those in real reservoirs to produce detectable flow rates in finite laboratory time. This may result in a high effective stress gradient that can cause non-uniform deformation of the pore system. To better understand the measured laboratory data, a theoretical model has been developed for calculating gas permeability of tight rock from laboratory measurements, which couples the effect of poroelastic deformation with the gas non-ideality and slippage effects. The proposed characteristic pressure model considers the poroelastic deformation and the real gas effects in the permeability calculation, which improves the accuracy of calculated permeability from laboratory measurements of tight rocks under large pressure gradients. The new model is validated by independent multiscale simulations, in which the poroelastic deformation and slippage effects are captured on the pore scale while the real gas behavior is captured on the core scale. The numerical results also indicate that the poroelastic deformation mainly affects the high-pressure region while the variation of gas properties dominates the low-pressure region. The new model is then applied to the calculation of gas permeability based on the laboratory measurements on coal and shale samples with non-ideal gas slippage and poroelastic effects considered. The poroelastic deformation and the real gas effect can be important as well as the slippage effect and the calculated apparent permeability will be overestimated if these two effects are neglected.